قابلية بعض أصناف الزيتون للإصابة بمرض عين الطاووس المتسبب عن الفطر Spilocaea oleagina (Cast) Hugh تحت ظروف العدوى الاصطناعية (Latakia University Journal -Biological Sciences Series, 2018)
To know the susceptibility of some olive varieties to peacock eye disease on sedlings of olive under artificial infection conditions, three varieties (Khadairy, Frentoyo, Zorzalina) were tested. The tested varieties varied during the incubation period. Planting infection was done on 1/11/2016. Where the first spot appeared on Khadairy after 81 days of infection and on Frentoyo after 94 days and c.v Zorzalina after 96 days. The tested varieties also varied in degree of susceptibility, where the rate of infection on the Khadairy variety in the last reading was 62.18% ,15.46% and 10.12% Respectively for the varieties Frentoyo and Zorzalina, As for the severity of the infection, the severity of the infection varied according to the tested varieties. In the last reading of Khadairy was 48.55%. Therefore, the cultivar was susceptible to peacock eye disease, and 7.86% for Frentoyo and therefore it was resistant to infection. and 4.41% for Zorzalina and was highly resistant to infection. تم اختبار ثلاثة أصناف زيتون (خضيري، فرنتويو ، زورزالينا) للتعرف على قابليتها للإصابة بمرض عين الطاووس على غراس زيتون بعمر سنة تحت ظروف العدوى الاصطناعية. تباينت الأصناف المختبرة في فترة الحضانة حيث تم إعداء الغراس بتاريخ 1/11/2016 و ظهرت اول بقعة على غراس الصنف خضيري بعد 81 يوماً من العدوى وعلى الصنف فرنتويو بعد 94 يوماً وللصنف زورزالينا بعد 96 يوماً ، كما تباينت الأصناف المختبرة في درجة قابليتها للإصابة حيث وصلت نسب الإصابة على الصنف خضيري في القراءة الأخيرة بعد (175 يوماً من العدوى) 62.18% وكانت 15.46 و 10.12% للصنفين فرنتويو وزورزالينا على التوالي، وتباينت شدة الإصابة أيضاً حسب الأصناف المختبرة حيث بلغت في القراءة الأخيرة للصنف خضيري 48.55% وبالتالي يعد الصنف خضيري قابل للإصابة بمرض عين الطاووس في حين بلغت للصنف فرنتويو 7.86% وبالتالي يعد مقاوم للإصابة بالمرض وبلغت في الصنف زورزالينا 4.41% ويعد عالي المقاومة للإصابة بالمرض.